Batter up, SpongeBob! - Lewman, David; McGee, Warner (New York : Simon Spotlight/Nickelodeon, 2011)
Remembering happy days playing T-ball, SpongeBob is eager to join his dad's team--until he finds out they're playing real baseball! Can he hit a home run and make his dad proud?
"Based on the TV series SpongeBob SquarePants created by Stephen Hillenburg as seen on Nickelodeon"--T.p. verso.
Keywords: SpongeBob SquarePants (Fictitious character); Fathers and sons - Juvenile literature; Baseball stories - Juvenile literature; Baseball - Juvenile literature; Fathers and sons; Marine animals - Juvenile literature